Drivers of provincial SO2 emissions in China – Based on multi-regional input-output analysis. (20th November 2019) - Liu, Qiaoling; Long, Yin; Wang, Chunrui; Wang, Zhen; Wang, Qin; Guan, Dabo
Abstract: Studying the driving factors of pollutant emissions is of great significance for China in the formulation of pollution control strategies. Existing studies mainly focus on the causes of national aggregate emission changes. However, considering the large differences among provinces in China and their close economic linkages, it is necessary to develop a provincial-level analysis to shape provincial policies for emission reduction. Using the multi-regional input-output (MRIO) tables of 30 provinces in China and adopting structural decomposition analysis, we analyze how changes in the end-of-pipe treatment, cleaner production, economic production structure, domestic final use, domestic exports and international exports drive national and provincial SO2 emissions. Decomposition results show that during 2002–2010 the absolute value of each effect based on the MRIO model is higher than that based on the national aggregate input-output model, which indicates that the existing studies adopting the national average data conceal the variation in the driving factors and underestimate their contributions to SO2 emission changes. The decomposition results based on MRIO model further show that the end-of-pipe treatment and cleaner production are the major emission reduction factors for all provinces, and the effect of the former has noticeably increased during 2007–2010. For the eastern provinces, interestingly, the economic production structure becomes a major emission reduction factor during the period of 2007–2010. Changes in domestic final demand, domestic exports and international exports exhibit significantly different contributions among provinces. The increased final demand in eastern provinces largely drive SO2 emissions for all provinces. Based on the above findings, policy implications that address the SO2 emission reduction issues are proposed. Highlights: Drivers of provincial SO2 emissions in China is examined by using MRIO-SDA. Large differences and close economic linkages among provinces in China are captured. Absolute value of decomposition results based on MRIO model were higher than that based on national aggregate IO model. Changes of economic production structures reduced SO2 emissions in the eastern provinces. The increased final demand in eastern provinces drove SO2 emissions for all provinces.